A catalogue of family and genus group names in Scolytinae and Platypodinae with nomenclatural remarks (Coleoptera: Curculionidae) - Onso-Zarazaga, Miguel A.; Lyal, Christopher H. C. (Zootaxa, 2009)
A list of available taxonomic names in Curculionidae: Scolytinae and Platypodinae in familyand genus-groups is given, together with some remarks on unavailable nominal taxa. Comments are provided on their status and nomenclature, and additions and corrections to extant catalogues given, as a first step for their inclusion in the electronic catalogue ‘WTaxa’. Available names, not recognised as such in current published catalogues, are: Mecopelminae Thompson, 1992; Trypodendrina Nunberg, 1954; Archaeoscolytus Butovitsch, 1929; Camptocerus Dejean, 1821; Coccotrypes Eichhoff, 1878 (April); Coptogaster Illiger, 1804; Cosmoderes Eichhoff, 1878 (April); Cryptoxyleborus Wood & Bright, 1992; Cylindra Illiger, 1802; Dendrochilus Schedl, 1963; Dendrocranulus Schedl, 1938; Doliopygus Browne, 1962; Doliopygus Schedl, 1972; Erioschidias Wood, 1960; Ernopocerus Wood, 1954; Idophelus Rye, 1877; Lepicerus Eichhoff, 1878 (April); Lepidocerus Rye, 1880; Miocryphalus Schedl, 1963; Ozopemon Hagedorn, 1910; Phloeoditica Schedl, 1963; Pinetoscolytus Butovitsch, 1929; Pycnarthrum Eichhoff, 1878 (April); Pygmaeoscolytus Butovitsch, 1929; Scolytogenes Eichhoff, 1878 (April); Spinuloscolytus Butovitsch, 1929; Stephanopodius Schedl, 1963; Stylotentus Schedl, 1963; Thamnophthorus Blackman, 1942; Trachyostus Browne, 1962; Treptoplatypus Schedl, 1972; Triarmocerus Eichhoff, 1878 (April); Trypodendrum Agassiz, 1846; Tubuloscolytus Butovitsch, 1929; Xelyborus Schedl, 1939. Unavailable names, not recognised as such in the current published catalogues, are: Chaetophloeini Schedl, 1966; Eidophelinae Murayama, 1954; Mecopelmini Wood, 1966; Strombophorini Schedl, 1960; Tomicidae Shuckard, 1840; Trypodendrinae Trédl, 1907; Acryphalus Tsai & Li, 1963; Adryocoetes Schedl, 1952; Asetus Nunberg, 1958; Carphoborites Schedl, 1947; Charphoborites Schedl, 1947; Cryptoxyleborus Schedl, 1937; Cylindrotomicus Eggers, 1936; Damicerus Dejean, 1835; Damicerus Dejean, 1836; Dendrochilus Schedl, 1957; Dendrocranulus Schedl, 1937; Doliopygus Schedl, 1939; Erioschidias Schedl, 1938; Ernopocerus Balachowsky, 1949; Gnathotrichoides Blackman, 1931; Ipites Karpiński, 1962; Isophthorus Schedl, 1938; Jugocryphalus Tsai & Li, 1963; Landolphianus Schedl, 1950; Mesopygus Nunberg, 1966; Micraciops Schedl, 1953; Miocryphalus Schedl, 1939; Mixopygus Nunberg, 1966; Neohyorrhynchus Schedl, 1962; Neophloeotribus Eggers, 1943; Neopityophthorus Schedl, 1938; Neoxyleborus Wood, 1982; Phloeoditica Schedl, 1962; Platypinus Schedl, 1939; Platyscapulus Schedl, 1957; Platyscapus Schedl, 1939; Pygodolius Nunberg, 1966; Scutopygus Nunberg, 1966; Stephanopodius Schedl, 1941; Stylotentus Schedl, 1939; Taphrostenoxis Schedl, 1965; Tesseroplatypus Schedl, 1935; Thamnophthorus Schedl, 1938; Thylurcos Schedl, 1939; Trachyostus Schedl, 1939; Treptoplatus Schedl, 1939. The name Tesseroceri Blandford, 1896, incorrectly given as “Tesserocerini genuini” in current catalogues, is unavailable as basionym for the family-group name, since it was proposed as a genusgroup name. Resurrected names from synonymy are: Hexacolini Eichhoff, 1878 from synonymy under Ctenophorini Chapuis, 1869 (invalid name because its type genus is a homonym) and given precedence over Problechilidae Eichhoff, 1878 under Art. 24.2; Hylurgini Gistel, 1848 from virtual synonymy under Tomicini C.G. Thomson, 1859 (unavailable name); Afromicracis Schedl, 1959 from synonymy under Miocryphalus Schedl, 1939 (an unavailable name) to valid genus; Costaroplatus Nunberg, 1963 from synonymy under Platyscapulus Schedl, 1957 (an unavailable name) to valid genus; Cumatotomicus Ferrari, 1867 from synonymy under Ips DeGeer, 1775 to valid subgenus of the same; Hapalogenius Hagedorn, 1912 from synonymy under Rhopalopselion Hagedorn, 1909 to valid genus; Pseudips Cognato, 2000, from synonymy under Orthotomicus Ferrari, 1867 to valid genus. New synonyms are: Hexacolini Eichhoff, 1878 (= Erineophilides Hopkins, 1920, syn. nov.); Hypoborini Nuesslin, 1911 (= Chaetophloeini Schedl, 1966, unavailable name, syn. nov.); Scolytini Latreille, 1804 (= Minulini Reitter, 1913, syn. nov.); Afromicracis Schedl, 1959 (= Miocryphalus Schedl, 1963, syn. nov.); Aphanarthrum Wollaston, 1854 (= Coleobothrus Enderlein, 1929, syn. nov.); Coccotrypes Eichhoff, 1878 (April) (= Coccotrypes Eichhoff, 1878 (December), syn. nov.); Cosmoderes Eichhoff, 1878 (April) (= Cosmoderes Eichhoff, 1878 (December), syn. nov.); Cumatotomicus Ferrari, 1867 (=Emarips Cognato, 2001, syn. nov.); Doliopygus Browne, 1962 (=Doliopygus Schedl, 1972, syn. nov.); Eidophelus Eichhoff, 1875 (= Idophelus Rye, 1877, syn. nov.); Hapalogenius Hagedorn, 1912 (= Hylesinopsis Eggers, 1920, syn. nov.); Phloeoborus Erichson, 1836 (= Phloeotrypes Agassiz, 1846, syn. nov.); Pycnarthrum Eichhoff, 1878 (April) (= Pycnarthrum Eichhoff, 1878 (December), syn. nov.); Scolytogenes Eichhoff, 1878 (April) (= Scolytogenes Eichhoff, 1878 (December) = Lepicerus Eichhoff, 1878 (December) = Lepidocerus Rye, 1880, synn. nov.); Trypodendron Stephens, 1830 (=Xylotrophus Gistel, 1848 = Trypodendrum Gistel, 1856, synn. nov.); Xylechinus Chapuis, 1869 (= Chilodendron Schedl, 1953, syn. nov.); Cosmoderes monilicollis Eichhoff, 1878 (April) (= Cosmoderes monilicollis Eichhoff, 1878 (December), syn. nov.); Hylastes pumilus Mannerheim, 1843 (= Dolurgus pumilus Eichhoff, 1868, syn. nov.); Hypoborus hispidus Ferrari, 1867 (= Pycnarthrum gracile Eichhoff, 1878 (April) syn. nov.); Miocryphalus agnatus Schedl, 1939 (= Miocryphalus agnatus Schedl, 1942, syn. nov.); Miocryphalus congonus Schedl, 1939 (= Miocryphalus congonus Eggers, 1940, syn. nov.); Lepicerus aspericollis Eichhoff, 1878 (April) = Lepicerus aspericollis Eichhoff, 1878 (December), syn. nov.); Spathicranuloides moikui Schedl, 1972 (June) (= Spathicranuloides moikui Schedl, 1972 (December), syn. nov.); Triarmocerus cryphalo-ides Eichhoff, 1878 (April) (= Triarmocerus cryphaloides Eichhoff, 1878 (December), syn. nov.); Scolytogenes darvini Eichhoff, 1878 (April) (= Scolytogenes darwinii Eichhoff, 1878 (December), syn. nov.). New type species designations are: Bostrichus dactyliperda Fabricius, 1801 for Coccotrypes Eichhoff, 1878 (April); Triarmocerus cryphaloides Eichhoff, 1878 (April) for Triarmocerus Eichhoff, 1878 (April); Ozopemon regius Hagedorn, 1908 for Ozopemon Hagedorn, 1910 (non 1908); Dermestes typographus Linnaeus, 1758 for Bostrichus Fabricius, 1775 (non Geoffroy, 1762). New combinations are: Afromicracis agnata (Schedl, 1939), A. attenuata (Eggers, 1935), A. ciliatipennis (Schedl, 1979), A. congona (Schedl, 1939), A. dubia (Schedl, 1950), A. elongata (Schedl, 1965), A. grobleri (Schedl, 1961), A. klainedoxae (Schedl, 1957), A. longa (Nunberg, 1964), A. natalensis (Eggers, 1936), A. nigrina (Schedl, 1957), A. nitida (Schedl, 1965), A. pennata (Schedl, 1953) and A. punctipennis (Schedl, 1965) all from Miocryphalus; Costaroplatus abditulus (Wood, 1966), C. abditus (Schedl, 1936), C. carinulatus (Chapuis, 1865), C. clunalis (Wood, 1966), C. cluniculus (Wood, 1966), C. clunis (Wood, 1966), C. costellatus (Schedl, 1933), C. frontalis (Blandford, 1896), C. imitatrix (Schedl, 1972), C. manus (Schedl, 1936), C. occipitis (Wood, 1966), C. pulchellus (Chapuis, 1865), C. pulcher (Chapuis, 1865), C. pusillimus (Chapuis, 1865), C. subabditus (Schedl, 1935), C. turgifrons (Schedl, 1935) and C. umbrosus (Schedl, 1936) all from Platyscapulus; Hapalogenius africanus (Eggers, 1933), H. alluaudi (Lepesme, 1942), H. angolanus (Wood, 1988), H. angolensis (Schedl, 1959), H. arabiae (Schedl, 1975), H. atakorae (Schedl, 1951), H. ater (Nunberg, 1967), H. baphiae (Schedl, 1954), H. brincki (Schedl, 1957), H. confusus (Eggers, 1935), H. decellei (Nunberg, 1969), H. dimorphus (Schedl, 1937), H. dubius (Eggers, 1920), H. emarginatus (Nunberg, 1973), H. endroedyi (Schedl, 1967), H. fasciatus (Hagedorn, 1909), H. ficus (Schedl, 1954), H. fuscipennis (Chapuis, 1869), H. granulatus (Lepesme, 1942), H. hirsutus (Schedl, 1957), H. hispidus (Eggers, 1924), H. horridus (Eggers, 1924), H. joveri (Schedl, 1950), H. kenyae (Wood, 1986), H. oblongus (Eggers, 1935), H. orientalis (Eggers, 1943), H. pauliani (Lepesme, 1942), H. punctatus (Eggers, 1932), H. quadrituberculatus (Schedl, 1957), H. rhodesianus (Eggers, 1933), H. saudiarabiae (Schedl, 1971), H. seriatus (Eggers, 1940), H. squamosus (Eggers, 1936), H. striatus (Schedl, 1957), H. sulcatus Eggers, 1944), H. togonus (Eggers, 1919), H. ugandae (Wood, 1986) and H. variegatus (Eggers, 1936), all from Hylesinopsis. New ranks are: Diapodina Strohmeyer, 1914, downgraded from tribe of Tesserocerinae to subtribe of Tesserocerini; Tesserocerina Strohmeyer, 1914, downgraded from tribe of Tesserocerinae to subtribe of Tesserocerini. New placements are: Coptonotini Chapuis, 1869 from tribe of Coptonotinae to tribe of Scolytinae; Mecopelmini Thompson, 1992, from tribe of Coptonotinae to tribe of Platypodinae; Schedlariini Wood & Bright, 1992, from tribe of Coptonotinae to tribe of Platypodinae; Spathicranuloides Schedl, 1972, from Platypodinae s.l. to Tesserocerina; Toxophthorus Wood, 1962 from Scolytinae incertae sedis to Dryocoetini. Confirmed placements are: Onychiini Chapuis, 1869 to tribe of Cossoninae (including single genus Onychius Chapuis, 1869); Sciatrophus Sampson, 1914 in Cossoninae incertae sedis; Cryphalites Cockerell, 1917 in Zopheridae Colydiinae. Corrected spellings are: Micracidini LeConte, 1876 for Micracini; Phrixosomatini Wood, 1978 for Phrixosomini. Gender agreements are corrected for species of several genera.